MONITORING DAN EVALUASI KINERJA GURU YANG EFEKTIF DI SEKOLAH SWASTA - Maulana, Muhamad Pandu; Sandra, Yopfie; Baharuddin, Baharuddin (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This research aims to dig information that can be used as a reference source of knowledge on monitoring and evaluation of effective teacher performance to be applied in schools. Basically, monitoring is one way to ensure quality performance. It is expected that the school's working environment will be improved with the presence of monitoring, review, and evaluation functions. in conducting joint activities by optimizing the role of monitoring and evaluation. Evaluation is crucial to assessing teacher performance. It makes it possible to improve and improve the performance of less-favoured teachers and improve better teacher performance to ensure quality education. The purpose of the evaluation is to provide an assessment and measurement of the performance that has been performed. Therefore, the term evaluation also means evaluation and measurement. In the research this time using qualitative method with the study of libraries as a source of information and reference used.